2004
DOI: 10.1017/s003118200300475x
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of cadmium and 3,3,4,4,5-pentachlorobiphenyl (PCB 126) on the humoral immune response in European eel (Anguilla anguilla) experimentally infected with larvae of Anguillicola crassus (Nematoda)

Abstract: The individual and combined effects of cadmium (Cd) and 3,3',4,4',5-pentachlorobiphenyl (PCB 126) on the antibody response of fish against metazoan parasites were tested. Eels experimentally infected with the swim bladder nematode Anguillicola crassus were exposed to sublethal concentrations of Cd and PCB 126. Cd was added to the water resulting in an effective concentration of 21.7 +/- 12.8 microg/l (mean +/- S.D.). PCB 126 was applied orally at a dose of approximately 100 ng PCB 126 per g body weight. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 68 publications
2
31
0
Order By: Relevance
“…Sagerup et al (2000) found positive correlation between PCB contamination of the habitat and intensity of nematode infection in gulls (Larus hyperboreus). Immunosuppression induced by PCB was experimentally confirmed by Sures and Knopf (2004). In this case, European eels (Anguilla anguilla) infected with the swim bladder nematode Anguillicola crassus were exposed to sublethal concentrations of PCB 126, which resulted in complete suppression of the antibody response in eels.…”
Section: Pcb Concentration In Perch and Parasitic Infectionmentioning
confidence: 89%
“…Sagerup et al (2000) found positive correlation between PCB contamination of the habitat and intensity of nematode infection in gulls (Larus hyperboreus). Immunosuppression induced by PCB was experimentally confirmed by Sures and Knopf (2004). In this case, European eels (Anguilla anguilla) infected with the swim bladder nematode Anguillicola crassus were exposed to sublethal concentrations of PCB 126, which resulted in complete suppression of the antibody response in eels.…”
Section: Pcb Concentration In Perch and Parasitic Infectionmentioning
confidence: 89%
“…In field studies, increased infection and disease incidence in benthic fish from various coastal areas has been associated with PCB contamination (Vethaak and Reinhalt 1992). In the case of eel, Sures and Knopf (2004) showed that a dose of 100 ng/g w.w. of PCB 126 suppress antibody response, thus increasing vulnerability to infection by A. crassus. Machut and Limburg (2008) found elevated infection rates when urbanized lands exceeded 15 % of the tributary catchment area, as in the case of the lower Tevere River, and suggested that urbanization may increase eel susceptibility to infection by increasing stressors.…”
Section: Pop Contaminationmentioning
confidence: 99%
“…So far only a small number of studies is focused on the joint effects of pollutants and parasites on eel health (Sures and Knopf 2004;Sures 2006;Sures et al 2006). This is an area that requires further investigation, as contaminant exposure can lead to a decrease in growth or impair the physiology of the immune system, causing an increased sensitivity to infectious diseases and parasites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the suppression of the host's antibody reaction is only beneficial for the parasite in its original eel host (i.e. A. crassus in Anguilla japonica, see Knopf and Lucius 2008) as no effect of the humoral immune response in European eels could be found (Knopf and Lucius 2008;Knopf et al 2000;Sures and Knopf 2004b).…”
Section: Discussionmentioning
confidence: 99%